Policy discrimination against the minority group of flows of believers citizens in Indonesia: an administrative justice perspective - Fx Hastowo Broto Laksito (Journal of Law, Environmental and Justice, 2023)
This study examines discrimination against aliran kepercayaan adherents in Indonesia, despite the Constitutional Court Decision Number 97/PUU-XIV/2016 recognizing their existence. This study found that human rights are inherent in humans and essential to life. Constitutional Court considerations include religious rights, particularly the right to believe in God Almighty, and affirmation that the rights are constitutional rights of citizens, not state gifts. The Constitutional Court also considered the definition of'religion' and 'belief' In conclusion, the Constitutional Court carefully and gradually applied Indonesian cultural values to the issue. The Constitutional Court believes the state should respect, preserve, and fulfill religious rights including the right to believe. The Constitutional Court Decision No. 97/PUU-XIV/2016 states that adherents of the faith have constitutional rights to embrace their beliefs and allows their status to be included in population administration documents, such as the electronic identity card. However, administrative service practices in Indonesia seem to still not be well implemented, which harms a sense of justice, especially administrative justice, which requires openness, confidentiality, transparency, justice, efficiency, accountability, consistency, participation, rationality, equality, and equal treatment.